In the Process of Forming a Person, Overcoming the Emotional State in The Family Environment - Abdullayeva Zuhro Ismoilovna; Kayumova Gozal Narzullayevna (Genius Journals, 2022)
The process of personal development, individual psychological characteristics, the influence of social environment. Stability of the family environment, overcoming emotional states, creating a psychological climate for a healthy life style in the family.
Keywords: Personality development; emotional experiences; characteristics; social environment